d)=\(\dfrac{\left(7\sqrt{3}-5\sqrt{11}\right)\left(8\sqrt{3}+7\sqrt{11}\right)}{\left(8\sqrt{3}-7\sqrt{11}\right)\left(8\sqrt{3}+7\sqrt{11}\right)}\)
=\(\dfrac{168+49\sqrt{33}-40\sqrt{33}-385}{192-539}\)=\(\dfrac{-217+9\sqrt{33}}{-347}\)
=\(\dfrac{217-9\sqrt{33}}{347}\)
e)=\(\dfrac{\left(3\sqrt{5}-2\sqrt{2}\right)\left(2\sqrt{5}+3\sqrt{2}\right)}{\left(2\sqrt{5}-3\sqrt{2}\right)\left(2\sqrt{5}+3\sqrt{2}\right)}\)
=\(\dfrac{30+9\sqrt{10}-4\sqrt{10}-12}{20-18}\)=\(\dfrac{18+5\sqrt{10}}{2}\)
e: \(\dfrac{3\sqrt{5}-2\sqrt{2}}{2\sqrt{5}-3\sqrt{2}}=\dfrac{18+5\sqrt{10}}{2}\)